The Influence of Online Customer Reviews and Live Streaming on Impulsive Buying Among Generation Z - Fauzan Manafi Albar; Cucu Hodijah; Rizki Chrisulianti; Galih Raspati; Umban Adi Jaya (Transpublika Publisher, 2026)
As social commerce platforms like TikTok Shop rapidly reshape how people shop online, Generation Z—digital natives who thrive on interactive content have become especially prone to spontaneous purchases. In this context, this study seeks to identify the bearing of Online Customer Reviews (OCR) and Live streaming upon impetuous purchasing proclivities among Generation Z habitués of TikTok Shop in Indonesia. The investigation employs an explanatory quantitative paradigm, with empirical data garnered through questionnaire instruments administered to 120 respondents conscripted via purposive sampling. Data analysis was executed through multiple linear regression alongside hypothetical corroboration procedures encompassing t-test and F-test analyses. The findings uncover that partially, Online Customer Reviews have a significant negative effect on Impulsive Buying, while Live streaming has a positive and significant effect. Taken together, both variables significantly shape Impulsive Buying, with a coefficient of determination of 44.3%. These findings indicate that Live streaming is the dominant factor in driving impulsive purchases, whereas Online Customer Reviews tend to enhance consumer rationality. This study implies that the integration of informational and interactive experiential marketing strategies is crucial in influencing consumer behavior in the era of social commerce.